Empirical Study of Ricardian Equivalence Hypothesis in Indonesia: The Effect of Budget Deficit on Public Consumption in 1990-2018 - Anisa Kurniarahman; Muhammad Anas (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2020)
Fiscal policy remains a central tool to boost the economy. Indonesia has implemented a deficit fiscal policy for the budget deficit, but Indonesia has not achieved the economic growth target. This reality shows that there is a gap between policy and policy outcomes. This research aims to prove the existence of the Ricardian Equivalence Hypothesis (REH), namely whether the fiscal policy, in this case, the budget deficit, affects public consumption. In addition to analyzing gross domestic product (PDB) as a measure of revenue, government debt, and budget deficits, researchers added variable deposit rates as one of the monetary policy instruments. The research employs Adaptive Expectation Model analysis that shows that in the short and long term, only variable deposit rates had a significant effect on public consumption, meaning that  other variables such as GDP, government debt, and budget deficits had no impact on public consumption in Indonesia for 1990-2018 period. Thus, this study validates the existence of Short Ricaermc both in the short and long term. With this result, the government must change the deficit policy strategy so that the results of productive spending can be enjoyed directly by the people. Some policies that should to maintain interest rates, not do too much debt, develop the country's industry, and country's  deficit budgets to things that directly support the economy Keywords: fiscal policy, budget deficit, Ricardian Equivalence Hypothesis, public consumption, Adaptive Expectation ModelJEL Clasification : E2, E62, H62